Net fluid flow and non-Newtonian effect in induced-charge electro-osmosis of polyelectrolyte solutions - Feng, Huicheng (2020)
This paper reports an interesting net fluid flow in the induced-charge electro-osmosis (ICEO) of poly(sodium 4-styrenesulfonate) (NaPSS) solutions measured through microparticle image velocimetry (μPIV). The net fluid flow is attributed to the significantly unequal cations and poly-anions of NaPSS. Owing to the phase delay effect of ions, different flow patterns appear with the alternating electric field. The inflow velocity and outflow velocity are found to be unequal and their relative magnitude shows a dependence on the electric field strength. The ICEO velocity is positively correlated with the NaPSS concentration. As NaPSS introduces the non-Newtonian effect, the well-known quadratic relationship between ICEO velocity and electric field strength in Newtonian fluids breaks. The ICEO velocity varies differently with the electric field strength as the NaPSS concentration changes. These new findings can contribute to the understanding of ICEO of complex fluids, e.g., biofluids.